A Retrospective Comparative Study of Surgical Management of 4 Part Proximal Humerus Fractures between Internal Fixation with Philos Plate and Hemi Replacement with Neers Prosthesis - Dr P Amarnath Reddy; Dr K.Siva Krishna; Dr.N. Priyanka (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Neer recommended open reduction and internal fixation (ORIF) for three-part fracture dislocations and primary hemiarthroplasty (HA) for four-part fracture dislocations and for fractures with greater than 50% of cartilage-covered articular defect. The current study was conducted to compare surgical management of four part proximal humerus fractures between internal fixation vs hemi replacement. Methods: The study is a hospital based retrospective case study, conducted in Government General Hospital, Kurnool during the period of June 2022 to June 2024. 30 patients (adults) presenting with proximal humerus fractures with a follow up period of minimum of 6 months and maximum of 18 months were included. After surgery, all patients were examined six weeks, three months, and six months later, as well as every two weeks until a fracture had healed. The constant Score were evaluated at each visit. A shoulder with affected arm X-ray was taken to check for fracture union and implant-bone interaction. Results: In this study maximum age was 80 years and a minimum of 50 years with an the average age of 64.4 years. Significant differences were observed in all complications between range of movements between the two groups. Average time taken for internal fixation by hemiarthroplasty procedure was 120mins as compared to Philos which was100minutes.Blood loss was measured in terms of suction drain collection and mop count. The average amount of blood loss was 216 ml for PHILOS procedure and 356 ml for HEMIREPLACEMENT procedure. Conclusions: the ROM pertaining to flexion, abduction, internal rotation, and external rotation for individuals with Philos plating was 17%, 20%, 4% and 4.6% higher than those who received Neer’s hemiarthroplasty. In conclusion, our study suggests that Philos plate osteosynthesis may have superior results than hemiarthroplasty when treating four-part proximal humerus fractures in individuals aged fifty and above.